Diversity-combining receiver for FFH/FSK systems over partial-band noise jamming and AWGN channels - Quah, Royston Wee Long. (2009)
In this report, bit-error-rate (BER) performance of a fast frequency-hopped frequency-shift-keying (FFH/FSK) system utilizing diversity-combining over a partial-band jamming (PBJ), additive white Gaussian noise (AWGN) and fading channel is studied. BER simulation is conducted for three diversity-combining methods, namely, hard-decision combining, square-law linear combining and product combining.